Dance. - Lepecki, André (London : Whitechapel Gallery, 2012)
"This collection surveys the choreographic turn in the artistic imagination from the 1950s onwards, and in doing so outlines the philosophies of movement instrumental to the development of experimental dance. By introducing and discussing the concepts of embodiment and corporeality, choreopolitics, and the notion of dance in an expanded field, Dance establishes the aesthetics and politics of dance as a major impetus in contemporary culture. It offers testimonies and writings by influential visual artists whose work has taken inspiration from dance and choreography."--Publlisher
Dance surveys the choreographic turn in the arts from the 1950s onwards, exploring the philosophies of movement instrumental to the development of experimental dance, the concepts of embodiment, corporeality, choreopolitics, and the notion of dance in an expanded field.
boek